“Banyak Anak Banyak Rejeki” vs “Dua Anak Cukup” Via Program KB di Kota Batam - Denok Maya Dewi (Journal of Law and Policy Transformation, 2017)
In order to solve the population problem particularly high population growth, the Government issued the Policy of Family Planning (KB). The implementation of KB programs in Indonesia is strengthened by the enactment of Law No. 52 of 2009 on Population Development and Family Development. Based on the Law, KB is interpreted as an attempt to regulate the child's birth, the distance and the ideal age to give birth, birth control through the promotion, protection and assistance in accordance with the reproduction rights to create quality family. The KB program aims to meet the demand for KB and reproductive health quality and controlling the birth rate, which in turn to improve the quality of people and small families. The purpose of this study was to analyze the implementation of Law No. 52 of 2009 on Population Development and Family Development to support the programs of KB services in Batam, as well as to discover the obstacles, support and solutions in the implementation of the policy. The data collection conducted by interviews and field observations with a sample of the KB Field Extension Workers (field officers) in Batam City. Based on the research results, the programs of KB services in the Batam City has not been effective because of the inadequate structure, substance and culture which are reflected as evidenced by Nomenlektur Family Planning Agency that has not stood itself, but it has embodied in the form of institutional insertion and the lack of resources, skills and abilities as well as a load-intensive tasks of Family Planning Officers in Batam City. Dalam rangka mengatasi masalah kependudukan khususnya tingginya pertumbuhan penduduk, Pemerintah mengeluarkan Kebijakan Keluarga Berencana (KB). Pelaksanaan program KB di Indonesia diperkuat dengan ditetapkannya Undang-Undang Nomor 52 Tahun 2009 tentang Perkembangan Kependudukan dan Pembangunan Keluarga. Berdasarkan Undang-Undang tersebut KB diartikan sebagai upaya mengatur kelahiran anak, jarak dan usia ideal melahirkan, mengatur kehamilan melalui promosi, perlindungan dan bantuan sesuai dengan hak reproduksi untuk mewujudkan keluarga yang berkualitas. Program KB bertujuan untuk memenuhi permintaan pelayanan KB dan Kesehatan Reproduksi (KR) yang berkualitas serta mengendalikan angka kelahiran yang pada akhirnya meningkatkan kualitas penduduk dan mewujudkan keluarga-keluarga kecil berkualitas. Tujuan penelitian ini adalah menganalisis implementasi Undang-Undang Nomor 52 Tahun 2009 tentang Perkembangan Kependudukan dan Pembangunan Keluarga dalam menunjang program pelayanan keluarga berencana di Kota Batam, serta menemukan hambatan-hambatan, penunjang dan solusinya dalam implementasi kebijakan tersebut. Pengumpulan data dilakukan secara wawancara dan observasi lapangan dengan sampel para Tenaga Penyuluh Lapangan Keluarga Berencana (PLKB) Kota Batam. Berdasarkan hasil penelitian bahwa pelayanan KB di Kota Batam belum efektif, di karenakan struktur, subtansi dan kultur yang tidak memadai, tercermin dengan Nomenlektur Badan Keluarga Berencana yang belum berdiri sendiri, tapi masih dalam bentuk penyisipan kelembagaan dan keterbatasan jumlah, kemampuan dan keterampilan serta beban tugas yang banyak dari petugas yang membidangi KB di Kota Batam.